2016
DOI: 10.1177/0954405416668924
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the mechanical properties of metallic lattice structures fabricated using selective laser melting

Abstract: An investigation of the mechanical properties of metallic lattice structures fabricated using selective laser melting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…It combined the characteristics of the cube and BCC/OC (Limmahakhun et al, 2017b;Wang L. et al, 2017). Adding vertical stiffeners through the center of the BCC/OC unit was also a way to improve the original BCC/OC (shown in Figure 1a 2 ) (Feng et al, 2016). All these reinforced BCC/OC scaffolds were better than the original BCC structures in compressive properties and Young's modulus.…”
Section: The Bcc/ocmentioning
confidence: 99%
See 1 more Smart Citation
“…It combined the characteristics of the cube and BCC/OC (Limmahakhun et al, 2017b;Wang L. et al, 2017). Adding vertical stiffeners through the center of the BCC/OC unit was also a way to improve the original BCC/OC (shown in Figure 1a 2 ) (Feng et al, 2016). All these reinforced BCC/OC scaffolds were better than the original BCC structures in compressive properties and Young's modulus.…”
Section: The Bcc/ocmentioning
confidence: 99%
“…The combination of FCC and BCC, named face and body-centered cube cell (FBCC)/with vertical struts (FBCCz), was another way of improvement. The mechanical properties were measured in the compression test, and the results indicated that FBCC/FBCCZ designed scaffold has higher stiffness than the original BCC/OC (Feng et al, 2016). Furthermore, the FBCCz designed scaffold showed the highest specific modulus, which meant that the structure provided superior performance for compressive load scenarios that attempt to optimize the stiffness-to-weight ratio (Mazur et al, 2015).…”
Section: The Bcc/ocmentioning
confidence: 99%
“…Knowing the mechanical properties of strut, finite element analysis could be develop to simulate the behavior of 316L scaffolds. In this way, the engineering stress-strain diagrams can be correlated with theoretical predictions of 316L scaffolds [49]. Future studies are required to evaluate the strut accuracy and imperfections by X-ray microtomography (micro-CT scanning) [50].…”
Section: Validating the Knowledgementioning
confidence: 99%
“…From a material point of view, previous SLM research has predominantly focused on lattice specimens made of Ti6Al4V [ 25 , 26 , 27 , 28 , 29 ], CoCr [ 30 , 31 ], and stainless-steel alloy [ 10 , 32 , 33 , 34 ]. Thanks to the modified chemical composition, Ti6Al7Nb alloy is characterized by higher corrosion resistance and bio-tolerance in comparison with Ti6Al4V [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%